A taxonomic reassessment of Chlamydomonas meslinii (Volvocales, Chlorophyceae) with a description of Paludistella gen.nov. - Susanti, Hani; Yoshida, Masaki; Nakayama, Takeshi; Nakada, Takashi; Watanabe, Makoto M. (Phytotaxa, 2020)
Chlamydomonas (Volvocales, Chlorophyceae) is a large polyphyletic genus that includes numerous species that should be classified into independent genera. The present study aimed to examine the authentic strain of Chlamydomonas meslinii and related strains based on morphological and molecular data. All the strains possessed an asteroid chloroplast with a central pyrenoid and hemispherical papilla; however, they were different based on cell and stigmata shapes. Molecular phylogenetic analyses based on 18S rDNA, atpB, and psaB indicated that the strains represented a distinct subclade in the clade Chloromonadinia. The secondary structure of ITS-2 supported the separation of the strains into four species. Based on the results, we propose a novel genus, Paludistella, including P. meslinii comb. nov., P. chlorostelatta comb. nov., P. asymmetrica sp. nov., and P. trianguloculus sp. nov.